2016
DOI: 10.1155/2016/7840759
|View full text |Cite
|
Sign up to set email alerts
|

Proteome Analysis of Date Palm (Phoenix dactyliferaL.) under Severe Drought and Salt Stress

Abstract: Date palm cultivars differently tolerate salinity and drought stress. This study was carried out to study the response of date palm to severe salinity and drought based on leaf proteome analysis. Eighteen-month-old date palm plants were subjected to severe salt (48 g/L NaCl) and drought (82.5 g/L PEG or no irrigation) conditions for one month. Using a protein 2D electrophoresis method, 55 protein spots were analyzed using mass spectrometry. ATP synthase CF1 alpha chains were significantly upregulated under all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 25 publications
2
16
0
Order By: Relevance
“…There are presently few omics studies of drought in date palm ( Table 1). A recent proteomics study identified genes involved in salt and drought tolerance in P. dactylifera (Rabey et al, 2016). The researchers challenged 3-month seedlings of the 'Sagae' cultivar with polyethylene glycol (82.5 g/L) and salinity (43 g/L) and identified 47 differentially expressed genes in the leaves.…”
Section: Omic Studies Of Water Shortage In Date Palmmentioning
confidence: 99%
“…There are presently few omics studies of drought in date palm ( Table 1). A recent proteomics study identified genes involved in salt and drought tolerance in P. dactylifera (Rabey et al, 2016). The researchers challenged 3-month seedlings of the 'Sagae' cultivar with polyethylene glycol (82.5 g/L) and salinity (43 g/L) and identified 47 differentially expressed genes in the leaves.…”
Section: Omic Studies Of Water Shortage In Date Palmmentioning
confidence: 99%
“…2 Drought affects a variety of vital physiological and biochemical processes in plants that cause a reduced growth and consequently a reduced final crop yield. 3,4,5 Al-Khayri and A-Bahrany. 6 stated that water availability is one of the principal limitations of crop production, particularly in the arid and semiarid regions where date palm is predominantly grown.…”
Section: Phoenix Dactylifera L (Date Palm) Belongs To the Genus Phoementioning
confidence: 99%
“…Due to its huge size, most physiological studies on date palm trees are achieved on seedling which originated from seed or tissue culture. 3,4,7,8 Al-Ka'aby and Abdul-Qadir. 7 studied the effect of water stress on callus induction from shoot tips of date palm (Phoenix dactylifera L.) cv.…”
Section: Phoenix Dactylifera L (Date Palm) Belongs To the Genus Phoementioning
confidence: 99%
See 1 more Smart Citation
“…In comparison, polyethylene glycol induced drought stress resulted in only 3 and 6 spots with higher and lower protein abundance, respectively. 115 Proteins involved in photosynthetic assimilation and protein synthesis declined in Chardonnay and Cabernet Sauvignon grapevines under water deficit and salinity stresses. Several proteins up regulated in tolerant cultivar Chardonnay were of an unknown function compared to Cabernet Sauvignon where proteins involved in protein metabolism were upregulated.…”
Section: Proteomicsmentioning
confidence: 99%